Generation of bioactive porous chitosan/gelatin based scaffold modified with tri-calcium phosphate/nano-bioglass for bone tissue engineering applications - Kumari S.; Srivastava P.; Mishra A. (My University, 2025)
In this study, as a novel approach, we developed chitosan and gelatin-based artificial biomimetic 3D structures that were crosslinked with EDC–NHS/glutaraldehyde solution and then loaded with freshly synthesized nanobioglass (NBG) and beta tri-calcium phosphate (ß-TCP) in three different ratios (1:0, 0:1 and 1:1) respectively. It was performed to develop a potential artificial acellular bone graft for load-bearing bones. This research study elucidates the preparation and properties of these novel acellular bone grafts. SEM studies showed that the developed scaffolds were porous with high interconnected pores between 220 and 265 μm and porosity greater than 80 ± 1.3%. XRD data showed the crystalline nature of NBG and ß-TCP which in turn affects the overall characteristics of the scaffolds biologically and structurally. Swelling study showed that the samples swelled about 40% in PBS and within 24 h, after which the swelling tendency got reduced. It was observed that after the addition of NBG and ß-TCP the swelling got reduced to almost 70%. Mechanical testing data revealed that the compressive modulus of the TCP/NBG scaffold was 2.7 ± 0.45 MPa, in a wet state which was better than many previous studies that were performed for developing load-bearing bone tissue scaffolds. Biodegradation studies depicted that after the addition of NBG and ß-TCP into the scaffolds the degradation rate reduced to around 59 ± 7% which was 71.1% in the Ch-G scaffold. Cell cytocompatibility assays indicated that the cell viability was not affected for the scaffolds even when the crosslinking solution contained glutaraldehyde. Alkaline phosphatase activity demonstrated enhanced osteogenesis after the addition of NBG and ß-TCP in 1:1 ratio to the scaffolds. Alizarin red staining showed that after the 1st week of cell culture the biomineralization was higher in NBG/TCP scaffolds. NBG and ß-TCP were never used together for scaffold development in bone tissue regeneration thus this novel NBG/TCP based biomaterial can be a potential biomaterial for bone regeneration applications. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.